Reduced glucocorticoid receptor expression in blood mononuclear cells of patients with borderline personality disorder - López-Villatoro, José Manuel; MacDowell, Karina S.; Diaz-Marsá, Marina; De La Torre-Luque, Alejandro; Prittwitz, Clara; Galvez-Merlin, Alejandra; Leza, Juan C.; Carrasco, Jose L. (Frontiers in Psychiatry, 2022)
Introduction Abnormal cortisol suppression in borderline personality disorder has been consistently reported in previous studies, suggesting that a hypersensitivity response of the hypothalamic-pituitary-adrenal (HPA) axis might occur in these patients. In this study, the abnormalities of the cortisol response in borderline personality disorder (BPD) are investigated through the cellular expression of the glucocorticoid receptors (GR) in BPD patients and its relationship with traumatic experiences. Methodology Sixty-nine male and female patients diagnosed with BPD and 62 healthy controls were studied. Peripheral blood mononuclear cells were obtained to investigate the expression of glucocorticoid receptors. Western blot was used to measure protein expression. Statistical correlations of GR expression with BPD clinical features and intensity of previous traumatic events were investigated. Results A significant decrease in the nuclear expression of glucocorticoid receptors was found in BPD patients compared to healthy controls in a regression analysis controlling for the effect of medication. GR expression decrease correlated significantly with clinical levels of anxiety and depression, but not with previous traumatic experiences in patients. Conclusions BPD patients had a lower nuclear expression of glucocorticoid receptors than healthy controls, when it was controlled for the effect of medication. The reduced GR expression in BPD patients was not associated with previous traumatic events and might be associated with other aspects of BPD, such as emotional instability; more studies with larger samples of patients are still needed to understand the relevance and the implications of these findings.